The Effectiveness of Mingle Game to Develop Students' Speaking Skills at SMPN 1 Indramayu - Dian Novitasari; Indra Yoga Prawiro (National Conference on Language, Education, and Technology Proceeding, 2022)
People need to talk to communicate with others by sharing their thoughts, ideas and feelings. Speaking is one of the most important language skills in learning English. Unfortunately, students find it difficult to express what they think using English including inhibition, inability to speak, low or uneven participation, and excessive use of mother tongue. Therefore, one of the games that can be used to teach speaking is the Mingle game. This study aims to determine the effectiveness of the mingle game in developing students' speaking skills. This research used a quantitative design.